Retinoblastoma in Adults: Clinical Features, Gene Mutations and Treatment Outcomes: A Study of Six Cases - Zhou, Nan; Yang, Lihong; Xu, Xiaolin; Liu, Yueming; Wei, Wenbin (Frontiers in Oncology, 2022)
Purpose: To report six Asian adult patients with retinoblastoma (RB). Design: Retrospective and observational small case series. Participants: Six patients with a white dome-shaped tumor of the retina were evaluated from May 10, 1995, to September 10, 2021. Main Outcome Measures: Initial tumor and associated fundus features, pathology, gene mutation, treatment, tumor course on follow-up, and salvage globe outcome. Results: The six affected Asian patients consisted of three men and three women. The mean age at the time of diagnosis was 36.5 years (median: 31 years, range: 20-55 years). All patients were unilateral. In all cases, the tumors were white, dome-shaped, with full-thickness retinal involvement, and mushroom-like protrusions into the vitreous cavity. The mean tumor thickness measured by ultrasonography was 4.5 mm (median: 3.2 mm, range: 3.2-6.8 mm). Associated characteristic symptoms included dilated retinal feeding artery and draining vein (100%), surrounding subretinal infiltration (83%), exudative retinal detachment (83%), and vitreous seeds (67%). Local tumor resection was performed in three patients, I-125 plaque brachytherapy combined with transpupillary thermotherapy (TTT) and intravitreous injection of melphalan (combination treatment) in one patient, I-125 plaque brachytherapy in two patients, and enucleation in one (20%) patient. RB1 gene testing was carried out on four patients and pathological diagnosis on five patients. Genetic analysis revealed that the RB1 mutation was a mosaic c.709dupG (p.Glu237GlyfsTer4) duplication in one patient, a mosaic c.763C>T(p.Arg255Ter) mutation in another patient, while the remaining two patients were RB1 negative. At the end of the follow-up, none of the patients had developed tumor-related metastasis or died. The findings were consistent in all patients who had an adequate follow-up. This study focused on this rare lesion to distinguish it from other intraocular white lesions in adults, including choroidal osteoma, vitreoretinal lymphoma, and retinal capillary hemangioma, all of which are different clinical entities. Conclusion: In adults, RB is typically a white, full-thickness retinal mass that is unilateral, often combining with retinal feeding vessels, subretinal infiltration, and vitreous seeds. Genetic studies on adult-onset RB are essential and still require elucidation. Despite RB being a malignant tumor, patient survival was minimally affected.